Service quality in leisure and tourism - Williams, C.; Buswell, J.; Buswell, J.; Williams, C. (Wallingford :CABI Publishing, 2003)
This book aims to develop knowledge and understanding of the theories and principles of service quality within the context of leisure and tourism. Suitable for students, researchers, leisure and tourism professionals, it relates the nature of the consumer experience to the planning, design and management of service delivery and critically evaluates the various quality management methods, systems, techniques and approaches that can be applied to the leisure and tourism business environment. While part 1 (chapters 1-6) establishes the challenges facing leisure and tourism managers in achieving service quality, part 2 (chapters 7-9) examines the skills and techniques of translating the understanding of consumers, quality and the nature of leisure and tourism experiences into appropriate products and services. Part 3 (chapters 10-14) takes the management of service quality beyond the design of services into the management of systems and procedures and the overall philosophy of organizations in their approach to quality. The book has a subject index.
Keywords: EE119 - Leisure, Recreation and Tourism Economics, (New March 2000); EE720 - Consumer Economics; UU700 - Tourism and Travel